DECOLONIZATION VIA NEW UNDERSTANDING OF SUFISM - N. T. Nurulla-Khodzhaeva (Vestnik MGIMO-Universiteta, 2018)
In examining such a multi-layered phenomenon as Islam (like any other religion) one finds themselves at the crossroads of competing views, between and beyond orthodox and reformist. A number of “invitations” for decolonization from prominent Sufis allows representing Islam not as a network of horrifying mujahedeens, but as a real and genuine discourse community. The topic of decolonization covers our common East-West colonial heritage as well as the colonial contemporaneity. Thus, in addition to Rumi and Nietzsche, the work relies on philosophers of Khorasan, composers of Tajikistan, and modern Western philosophers of decolonization to build a strong basis for the topic. Sufi decolonization not only provides an opportunity to imbue the Platonic project on the connection between ontology and epistemology but also produces a possibility for constructive awareness of everything that was, and is, for the benefit of me-you, community, and communion of communities. This vision indicates the need for a multitude of combinations of knowledge and experiences, as well as for consideration of constant movements of the former and the latter. The lack of “multiplicity” in today’s world pushes us to a place, where we might at once get used to devices that “think” for us and “listen” to each other for us. The simplicity of such a picture is that this vision of society (and history) does not blame current “deafness,” but rather proposes for all of us, not only Muslims, to recognize the need to “return” to the ability to “listen” to each other. Within this framework, the article demonstrates the significance of the art of listening (as in the Arabic, sama), which embodies a double mysticism - the ability to listen with both ears and heart. On this basis the project of the intellectual community is being proposed; a project rooted in an organic unity of man and the world, which Ibn Sina described as odam va olam (in Tajik-Persian language). In these series of “invitations” through the prism of the heritage of east-west philosophy, there is an aim not to shelter oneself from the Eurocentric western theory of International Relations (IR), but rather to provide an opportunity to think about building a “post-Western” project, or otherwise a project based on the union between man and world (in Tajik-Persian, odam va olam).